Multiple genes for functional delta6 fatty acyl desaturases (Fad) in Atlantic salmon (Salmo salar L.): Gene and cDNA characterization, functional expression, tissue distribution and nutritional regulation - Monroig, Oscar; Zheng, Xiaozhong; Morais, Sofia; Leaver, Michael; Taggart, John; Tocher, Douglas R (Biochimica et Biophysica Acta (BBA) - Molecular and Cell Biology of Lipids, 2010)
Fish are the primary source in the human food basket of the n-3 long-chain polyunsaturated fatty acids (LC-PUFA), eicosapentaenoate (EPA; 20:5n-3) and docosahexaenoate (DHA; 22:6n-3), that are crucial to the health of higher vertebrates. Atlantic salmon are able to synthesis EPA and DHA from 18:3n-3 through reactions catalyzed by fatty acyl desaturases (Fad) and elongases of very long fatty acids (Elovl). Previously, two cDNAs encoding functionally distinct Δ5 and Δ6 Fads were isolated, but screening of a genomic DNA library revealed the existence of more putative fad genes in the Atlantic salmon genome. In the present study, we show that there are at least four genes encoding putative Fad proteins in Atlantic salmon. Two genes, Δ6fad_a and Δ5fad, corresponded to the previously cloned Δ6 and Δ5 Fad cDNAs. Functional characterization by heterologous expression in yeast showed that the cDNAs for both the two further putative fad genes, Δ6fad_b and Δ6fad_c, had only Δ6 activity, converting 47 and 12 % of 18:3n-3 to 18:4n-3, and 25 and 7 % of 18:2n-6 to 18:3n-6, for ∆6Fad_b and Δ6Fad_c, respectively. Both ∆6fad_a and ∆6fad_b genes were highly expressed in intestine (pyloric caeca), liver and brain, with ∆6fad_b also highly expressed in gill, whereas ∆6fad_c transcript was found predominantly in brain, with lower expression levels in all other tissues. The expression levels of the ∆6fad_a gene in liver and the ∆6fad_b gene in intestine were significantly higher in fish fed diets containing vegetable oil compared to fish fed fish oil suggesting up-regulation in response to reduced dietary EPA and DHA. In contrast, no significant differences were found between transcript levels for ∆6fad_a in intestine, ∆6fad_b in liver, or ∆6fad_c in liver or intestine of fish fed vegetable oil compared to fish fed fish oil. The observed differences in tissue expression and nutritional regulation of the fad genes were discussed in relation to gene structures and fish physiology.